Study of surface influence on the n-Ge(110) electroreflectance spectra and their polarization spectroscopy - Vlasenko, O.I.; Gentsar, P.O.; Stronski, A.V. (Functional Materials, 2009)
The contribution of the real (preliminary chemically etched) (110) surface of n-Ge into electroreflectance effect (energy range 1.9-2.6 eV) basing on polarization anisotropy of electrooptical effect has been separated under assumption that the surface electroreflectance component is isotropic while the bulk component of electroreflectance is anisotropic with respect to the light polarization vector orientation. The influence of the surface state on the anisotropic electroreflectance spectra, form changes of the subsurface potential barrier and internal mechanical stresses after mechanical polishing have been considered. Electron parameters of the n-Ge(110) subsurface layer are determined. Відокремлено внесок реальної (попередньо хімічно травленої) поверхні n-Ge(110) в ефект електровідбивання (енергетичний діапазон 1,9-2,6 еВ) на основі поляризаційної (тензорної) анізотропії електрооптичного ефекту у припущенні, що поверхнева складова електровідбивання (ΔR/ R)s (за яку несе відповідальність лінійний електрооптичний ефект, що пов'язаний з поверхнею п-Gе(110))-ізотропна, а об'ємна складова електровідбивання (за яку несе відповідальність ефект Келдиша-Франца) анізотропна відносно орієнтації вектора поляризації світлової хвилі. Проаналізовано вплив стану поверхні на анізотропні спектри електровідбивання, зміну форми приповерхневого потенціального бар'єру та внутрішніх механічних напружень після механічної поліровки. Визначено електронні параметри приповерхневого шару n-Ge(110). Разделен вклад реальной (предварительно химически травленной) поверхности n-Ge (110) в эффект электроотражения (энергетический диапазон 1,9-2,6 эВ) с использованием поляризационной (тензорной) анизотропии электрооптического эффекта в предположении, что поверхностная составляющая электроотражения изотропна, а объемная составляющая электроотражения анизотропна относительно ориентации вектора поляризации световой волны. Проанализировано влияние состояния поверхности на анизотропные спектры электроотражения, изменение формы приповерхностного потенциального барьера и внутренних механических напряжений после механической полировки. Определены электронные параметры приповерхностного слоя n-Ge(110).